Child’s oxytocin response to mother-child interaction: The contribution of child genetics and maternal behavior - Baião, Rita (2019)
The oxytocinergic system is a primary biological system involved in regulating a child's needs for bonding and for protection from threats. It is responsive to social experiences in close relationships, though evidence across studies is not entirely consistent. Guided by previous literature, we investigated individual and environmental factors predicting and presumably affecting children's oxytocin (OT) response during mother-child interaction. by focusing on children's OXTR genotype, and maternal behavior, respectively. This was achieved by assessing salivary OT levels of 88 Portuguese preschoolers prior to and following a mother-child interaction task, and by genotyping children's OXTR SNP rs53576. Maternal interactive behavior was assessed using Ainsworth scales. Results indicated that child genotype and mother's sensitive responsiveness interacted in predicting change in child OT concentrations from before to after the interaction. Specifically, Genotypic differences emerged under conditions of low maternal sensitive responsiveness: OT levels increased over time for children with the GG genotype when maternal sensitive responsiveness was low, but no such genotypic differences were evident when mothers were highly sensitive responsive. Findings provide preliminary support for the notion that increased understanding of children's OT and close relationships requires consideration of both individual and environmental factors.